Production and Quality in Squash Fruity 'Type Butternut' with Fruiting Induced by Cytokinin and Auxin - Diogenes Damarsio Andrade de Sousa; Francisco Hevilásio Freire Pereira; Roberto Cleiton Fernandes de Queiroga; Gisele Lopes dos Santos; Joyce Emanuele de Medeiros Fernandes; Whashington Idalino da Silva; Alzira Maria de Sousa Silva Neta; George Alves Dias (Brazilian Archives of Biology and Technology)
Abstract The need for a pollinator is a problem for cucurbit producers, as productivity depends on the efficiency of natural or artificial pollination. Growth regulators are gaining more and more importance in inducing fruiting in cucurbits, and can be an alternative for producers to increase their productivity. The objective of this work was to evaluate the effect of applying cytokinin (CPPU) and auxins (AIB and 2,4-dichlorophenoxyacetic acid) on inducing fruiting in butternut pumpkin. The application of 10 mg l-1 of IBA (indole-3-butyric acid) via the flower on the external part provides greater mass and length of the fruit, ensuring greater production of butternut pumpkin. The application of 3.0 mg l-1 of CPPU (N-(2-chloro-4-pyridyl)-N'-phenylurea) via the flower in the internal part results in a greater number of fruits. The physicochemical quality of butternut pumpkin fruits is not influenced by the application of auxins (AIB and 2,4-dichlorophenoxyacetic acid) and cytokinin (CPPU).